IMPLEMENTASI METODE OPERASI MORFOLOGIS DALAM PERBAIKAN HASIL SEGMENTASI CITRA DIGITAL GORGA BATAK - Sihombing, Ojahan; Buulolo, Efori; Siburian, Henry Kristian (STMIK Budi Darma, 2018)
As the development of research technology on Digital Image Processing continues to grow. Likewise, the improvement of the quality of sharpness / subtlety of the Gorga Batak images is an important thing to improve. This is one of the ways to preserve the Batak tribe area so that Gorga-gorga are still remembered and more interpreted. The cause of the need to be improved is the image of Gorga Batak is caused by several factors that cause the image to be less beautiful if it is interpreted by human beings such as the shape has been blurred (dark) due to shooting / shooting, has noise black spots on the image (noise), and the color is dull out of date. As an effort to improve image, the segmentation process is carried out by doing edge detection on the image, then the Morphological Operation Method will be implemented as one of the methods in Digital Image Processing that implements image quality improvement based on the shape and structure of the image. In this image processing, the Dilation Operation Technique and Operation Technique will be carried out. In Operation Dilation Techniques works by adding several segments (pixels) in the image so as to increase the integrity / sharpness of the structure of the image. While the Erosion Operation Technique will reduce / refine unnecessary parts / segments of the image so that the resulting image looks smoother, so that it can be more interpreted by humans and can be reused both as documentation of regional culture and so on. Using this method is expected to be able to improve and improve the quality / sharpness of Citra Gorga Batak. To facilitate the operation of the program design tools will be used, namely Matlab.Keywords: Image Improvement, Gorga Batak, Morphological Operation Method